Sustainable food consumption behavior in Indonesia: An approach theory of planned behavior - Ahmad Nuh; Mohamad Rizan; Karuniana Dianta A. Sebayang; Suparno Suparno; Muhammad Misbakul Munir (Journal of Business Management Education (JBME), 2023)
This research study aims to investigate sustainable food consumption behavior among generational groups in Indonesia using the approach of the Theory of Planned Behavior (TPB). The study proposes a set of attributes to enhance sustainable consumption in the Indonesian food industry and assesses the interrelationships among the attributes to promote sustainable food consumption behavior. An online poll was undertaken, with a sample size of 244 people. Partial-least squares structural equation modeling (PLS-SEM) was used to analyze the data using SmartPls. The findings show that perceived sustainability benefits affect attitude toward behavior. The three TPB variables have a positive influence on sustainable purchase intention. Consumer intention to buy sustainable food is most strongly influenced by perceived behavior control, followed by attitude toward behavior and subjective norms as the weakest variable.